2005
DOI: 10.3354/meps298189
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of closed area protection for a population of scallops

Abstract: Despite the current interest in using closed areas for fisheries management, few studies have actually examined the benefits for invertebrate fisheries such as scallops. This study details the dynamics of a population of great scallops Pecten maximus (L.), within a closed area and an adjacent fished area off the Isle of Man, over a 14 yr period (1989 to 2003). Scallop densities were very low in both areas when the closed area was set up, but increased at an accelerated rate over time within the closed area. Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 47 publications
1
45
1
Order By: Relevance
“…Greater stakeholder involvement is required for the successful establishment and management of MPAs (Jones 1999;Jones and Burgess 2005;Beukers-Stewart et al 2005). In the case of Lyme Bay, the multiplicity of direct and indirect interests means that there is a need to include more people in the decision making process, such as recreational users and local businesses.…”
Section: Discussionmentioning
confidence: 99%
“…Greater stakeholder involvement is required for the successful establishment and management of MPAs (Jones 1999;Jones and Burgess 2005;Beukers-Stewart et al 2005). In the case of Lyme Bay, the multiplicity of direct and indirect interests means that there is a need to include more people in the decision making process, such as recreational users and local businesses.…”
Section: Discussionmentioning
confidence: 99%
“…However, modeling results suggest that spillover effects may be greatest, but most difficult to detect, in cases where dispersal distances are long relative to reserve size. A review of existing empirical evidence is consistent with the implications of these theoretical findings: that detecting larval export in field studies is likely to be very challenging except when the increase in production within reserves is exceptionally large (9-12, 15-18, 37), the mean dispersal scale is not too long relative to reserve size (9-11, 13, 14), or sampling designs take advantage of directional dispersal and employ a suite of sampling sites at the appropriate spatial scale (9,12,13,(15)(16)(17)(18)37).…”
Section: Discussionmentioning
confidence: 99%
“…At the center of this debate is the suggestion that larvae from highly productive populations in marine reserves may move outside reserves and enhance populations in harvested areas (7,8). A few studies have demonstrated spatial and/or temporal patterns of recruitment or abundance that suggest larvae exported from reserves can enhance nearby fished populations (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). However, the larval export effect remains controversial (3), in part because empirical evidence remains limited (6).…”
mentioning
confidence: 99%
“…Mar Ecol Prog Ser 463: [159][160][161][162][163][164][165][166][167][168][169][170][171][172][173][174][175] 2012 grounds (Gell & Roberts 2003, Beukers-Stewart et al 2005, Pelc et al 2009). …”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…The positive effects of spatial management tools, such as marine reserves, on recovery of exploited stocks have been documented world-wide (Gell & Roberts 2003, Lester et al 2009, Aburto-Oropeza et al 2011), particularly in sessile or sedentary stocks (Lester et al 2009). For mobile species, adjacent fished areas might benefit from density-dependent spillover (Gell & Roberts 2003, Hilborn et al 2004, whereas both mobile and sedentary species may benefit from enhanced recruitment through larval dispersal from protected spawning grounds (Gell & Roberts 2003, Beukers-Stewart et al 2005, Pelc et al 2009). …”
Section: Introductionmentioning
confidence: 99%